Modifiers of stress related to timing of diagnosis in parents of children with complex congenital heart disease. (17th October 2016) - Pinto, Nelangi M.; Weng, Cindy; Sheng, Xiaoming; Simon, Kimberly; Byrne, Janice B.; Miller, Thomas; Puchalski, Michael D.
Abstract: Objective : Prenatal diagnosis of congenital heart disease (CHD) reportedly increases parental stress compared with postnatal diagnosis. We investigated the association of timing of diagnosis with parental stress and modifiers of this relationship. Methods : We enrolled parents with a fetus/infant diagnosed prenatally (Group 1) or postnatally (Group 2) with CHD requiring intervention prior to newborn discharge. Parents completed a Basic Symptom Inventory (BSI) – at diagnosis, birth, and follow-up. Adjusted mixed effects regression models compared scores. Results : The BSI was completed by 105 families (Group 1, n = 60 and Group 2, n = 45). On regression modeling, anxiety and global stress were lower in Group 1 (effect size −0.19 to −0.62) at diagnosis and birth though not at follow-up. When stratified by gender, Group 1 scores for anxiety and stress were primarily lower in fathers. Within Group 1, mothers scored higher in all domains and later gestational age at diagnosis was associated with higher anxiety and stress. Conclusions : Contrary to prior reports, parents of prenatally diagnosed infants with CHD had lower anxiety and stress than those diagnosed postnatally after adjusting for severity. Identifying those most vulnerable and modifiable risk factors will allow us to appropriately target psychosocial services for families with a CHD diagnosis.